Coupling of chemical, electrochemical and theoretical approach to study the corrosion inhibition of mild steel by new quinoxaline compounds in 1 M HCl. Issue 5 (May 2020) - Laabaissi, T.; Benhiba, F.; Missioui, M.; Rouifi, Z.; Rbaa, M.; Oudda, H.; Ramli, Y.; Guenbour, A.; Warad, I.; Zarrouk, A.
Abstract: The corrosion inhibition displays of two quinoxaline derivatives, on the corrosion of M-steel (M-steel) in 1 M HCl was studied by gravimetric, electrochemical, scanning electron microscopy (SEM), functional density theory (DFT) and molecular dynamic simulation (MD). The inhibitory efficacy increases with decreasing temperature and increases with inhibitor concentration and reached to 96 % (NSQN) and 92 % (CSQN) at 303 K and the optimum concentration (1×10-3 M). Ultraviolet–visible (UV–vis) spectroscopic analyses confirmed the presence of chemical interactions between the inhibitors and MS surface. The adsorption of NSQN & CSQN on the metallic surface obeys the Langmuir isotherm. A potentiodynamic polarization study confirmed that the inhibitors are of mixed-kind inhibitors. Theoretical computation (DFT) and molecular dynamics simulation (MD) are utilized to understand the mechanism of inhibition. Abstract : Electrochemistry; Theoretical chemistry, Quinoxaline derivatives; Mild steel; Corrosion inhibition; SEM/EDX; Simulation dynamics molecular